Temporomandibular joint disc displacement with reduction: a review of mechanisms and clinical presentation - Rodrigo Lorenzi POLUHA; Giancarlo De la Torre CANALES; Yuri Martins COSTA; Eduardo GROSSMANN; Leonardo Rigoldi BONJARDIM; Paulo César Rodrigues CONTI (Journal of Applied Oral Science, 2019)
Abstract Disc displacement with reduction (DDWR) is one of the most common intra-articular disorders of the temporomandibular joint (TMJ). Factors related to the etiology, progression and treatment of such condition is still a subject of discussion. This literature review aimed to address etiology, development, related factors, diagnosis, natural course, and treatment of DDWR. A non-systematic search was conducted within PubMed, Scopus, SciELO, Medline, LILACS and Science Direct using the Medical Subjective Headings (MeSH) terms “temporomandibular disorders”, “temporomandibular joint”, “disc displacement” and “disc displacement with reduction”. No time restriction was applied. Literature reviews, systematic reviews, meta-analysis and clinical trials were included. DDWR is usually asymptomatic and requires no treatment, since the TMJ structures adapt very well and painlessly to different disc positions. Yet, long-term studies have shown the favorable progression of this condition, with no pain and/or jaw locking occurring in most of the patients.